Optimalisasi Penerapan Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) dalam Pelaksanaan Program dan Penganggaran pada Poltekkes Kemenkes Mamuju - Muh. Firdaus; Andi Sinrang; Muhammad Nur (Public Inspiration : Jurnal Administrasi Publik, 2026)
The digitalization of public financial management has become a strategic imperative in Indonesia, exemplified by the implementation of the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI). This study examines the optimization of SAKTI implementation at Politeknik Kesehatan (Poltekkes) Kemenkes Mamuju, with the objectives of analyzing the level of SAKTI utilization and identifying obstacles alongside their solutions. Employing a qualitative research design with data collection through observation, in-depth interviews with five informants, and library research, this study analyzed findings using the Miles and Huberman model. The theoretical framework is grounded in Diffusion of Innovations (DOI) Theory by Rogers (2003), with analysis structured around five attributes: relative advantage, compatibility, complexity, trialability, and observability. Results reveal that SAKTI utilization remains limited to core financial units and has not been evenly distributed across all work units. Key constraints include limited human resource capacity in digital literacy, inadequate IT infrastructure, bureaucratic resistance to change, unstable network connectivity, and data synchronization issues. These findings indicate that SAKTI adoption remains administrative in character rather than institutionally embedded. Optimization requires a comprehensive approach encompassing capacity building, infrastructure upgrades, and organizational change management.